Administrative law challenges of post-clearance audit in Serbia - Cucić Vuk (Anali Pravnog Fakulteta u Beogradu)
Most imported/exported goods are not controlled by customs authorities at the border. This allows for the fast release of goods and the better functioning of international trade. The backbone of this system consists of customs declarations filed by the importers/exporters, selective control at the border, based on risk assessment, and the post-clearance audit (PCA) of the accepted customs declarations. This paper deals with the questionable practice of the Serbian Customs Administration with regard to the conducting of the PCA, particularly its relation with the Law on General Administrative Procedure and the issues related to the classification of goods according to customs tariff. The author identifies issues regarding the transparency, interpretation and implementation of the PCA in Serbia and contests the (internationally recognized) practice of changing the classification of goods in accepted customs declarations. The author proposes possible solutions for identified challenges.